Compositionality in the morphosemantic description of lexical structures: some questions about transparency of Croatian vocabulary - Raffaelli, Ida (Array, 2012)
Compositionality as a feature which underlies the morphosemantic structure of most of the Croatian words could be described as a gradable category. Since Croatian is a morphologically rich language suffixes and prefixes can be used in the formation of a new lexeme in many different ways. Therefore this paper claims that the morphological and the semantic nature of composite elements could be more or less transparent in the morphosemantic architecture of a new lexeme. It is our hypothesis that the degree of compositionality depends on a) frequency and productivity of both stem and morpheme b) transparency of the meaning of stem and morpheme, c) semantic shift of the motivated word with respect to the unmotivated word.